Prescripción de la Acción del Cobro, en las Pensiones Alimenticias Impagadas, ¿Equilibrio Jurídico o Vulneración al Derecho de Alimentos?” - Jiménez Achupallas, Miryam Patricia (2018)
This research work corresponds to a legal, doctrinal and comparative law study, titled, “Prescription of the Collection Action, Unpaid alimony, Legal Balance or Violation of the Right to Food?”, showing how it affects collections exuberant of arrears of alimony payments to the fed and that in turn they do not fulfill their purpose, allowing several years to demand compliance. I have elaborated an approach, in terms of the accumulation of alimony pension arrears and the passivity of who is in the obligation to demand compliance and does not, to verify the issue raised a general objective and three specific objectives of the, in the same way, surveys were carried out aimed at legal professionals, experts in the civil field and family, giving favorable criteria arguing that the prescription of the action of collection of arrears of alimony payments, do not violate the right to food, being very different the case of the arrears of alimony, which are within the human trade and are susceptible to prescription. The present thesis has an orientation from the social, economic and legal point of view, based on the study of comparative law legislation as well as comparative jurisprudence , demonstrating that countries such as Chile, Argentina, Peru, Spain have incorporated their rule, specifically in the Civil Code, and in their pertinent foundation cite; prescribes in five years the action 5 of exercising the recovery of unpaid alimony payments issued by judicial decision, the same ones that gave me information to make recommendations and propose, the respective legal reform of article of the Ecuadorian Civil Code in which it is not clear, but if there is the door to the prescription of overdue alimony, in which quotation the alimony can be waived and compensated ... without prejudice to the prescription that belongs to the debtor, with the prescription of the collection action, the legislators of the aforementioned countries , adopted this measure in order to protect the legal security established in the Contitution and above all to protect social peace.